The Holy Quran and the life of the Arabic language: A vision in translation and meaning - Mebarki, Mohamed (Journal of Human Sciences, 2022)
History monitors the pursuit of the many attempts to translate the Noble Qur’an into many languages. The authors of these translations think that the texts of the Qur’an are like the rest of the human texts. With its wording and meanings from the inspiration of the human mind, they made a mistake in their endeavors, which inevitably led him to distort the texts of the Qur’an and scatter its meanings here and there, and this leads to underestimating its language, rhetoric and eloquence. These texts, they have, are a cultural product produced by the human mind, or it is copied from previous books of the Almighty Qur’an - about that - and therefore this research aims to establish a brilliant future for the Arabic language as the only standard for understanding the language of the Qur’an and its translation, and to the scientific contributions on which the Arabic language bets. ; An extension of its civilization path under the banner of the Qur’an, carrying its expressions and meanings, and the efforts of active scholars who are loyal to the Qur’an and the language of the Qur’an.